Characterization of immune response in Staphylococcus aureus chronically infected bovine mammary glands during active involution - Andreotti, Carolina Soledad (2017)
The aim of this study was to characterize the immune response in Staphylococcus aureus chronically infected bovine mammary glands during active involution. Twenty-one Holstein non-pregnant cows in late lactation either uninfected or with chronic naturally acquired S. aureus intramammary infections (IMI) were included in this study. Cows were slaughtered at 7, 14 and 21 d after cessation of milking and samples for immunohistochemical analysis were taken. Protein expression of toll-like receptor 2 (TLR2) and TLR4 was significantly higher in S. aureus-infected quarters than in uninfected controls at the three involution stages studied. Protein expression of tumor necrosis factor-alpha (TNF-α), interleukin (IL)-1α and IL-17 was significantly affected by IMI; being higher in S. aureus-infected than uninfected quarters during all evaluated stages. In S. aureus-infected and uninfected quarters protein expression of lactoferrin increased from day 7–14 of involution, decreasing significantly to day 21 in mammary quarters with chronic infections. The number of monocytes-macrophages was significantly higher in S. aureus-infected than in uninfected control quarters at 7 and 21 d of involution. The number of T lymphocytes was significantly higher in S. aureus-infected than in uninfected quarters at 7 and 14 d of involution while the number of B lymphocytes was significantly higher in S. aureus-infected than in uninfected quarters during all evaluated stages, showing a progressive increase as involution advanced. These results demonstrated a sustained and exacerbated innate and adaptive immune response during chronic S. aureus IMI, playing a critical role in the infection control during active involution.